2005
DOI: 10.1088/0957-4484/16/9/012
|View full text |Cite
|
Sign up to set email alerts
|

Towards high sedimentation stability: magnetorheological fluids based on CNT/Fe3O4nanocomposites

Abstract: CNT (carbon nanotube)/Fe3O4 nanocomposites were prepared. The diameter of the CNT/Fe3O4 composites prepared was about 60 nm, while the diameter of the CNTs was about 20 nm according to the results of transmission electron microscopy (TEM) measurements. The average apparent density of the CNT/Fe3O4 nanoparticles was about 1.8 g cm−3, which is only a quarter of that normally used for magnetic particles. The sedimentation and magnetorheological properties of magnetorheological (MR) fluids based on CNT/Fe3O4 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 7 publications
0
64
0
Order By: Relevance
“…Magnetite (Fe 3 O 4 ) nanoparticle has broad applications such as high-density information storage, ferrofluid, catalysis, electronic devices, biomedical and pigments [2][3][4][5][6]. The crystal structure of magnetite is inverse spinel with space group of Fd-3m with lattice parameters a=b=c around 8,396 Å [7].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) nanoparticle has broad applications such as high-density information storage, ferrofluid, catalysis, electronic devices, biomedical and pigments [2][3][4][5][6]. The crystal structure of magnetite is inverse spinel with space group of Fd-3m with lattice parameters a=b=c around 8,396 Å [7].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, in MR fluids, magnetic particles, such as iron, iron oxides (Fe2O3 and Fe3O4), and carbonyl iron (CI), have been developed owing to their high saturation magnetization and suitable magnetic properties [50][51][52][53]. In addition, recent efforts on various composites with magnetic particles with different morphologies have been made to improve the stability of MR suspensions.…”
Section: Methodsmentioning
confidence: 99%
“…CNT/Fe3O4 nanocomposites have been reported [53], and Fe3O4/PMMA composite particles were fabricated successfully using a simple one-pot hydrothermal method [78], shown in Figure 2g,h, respectively. Detailed experimental and theoretical research about the MR characteristics of fiber suspensions have been reported, and the fiber suspensions have a positive effect on the MR performance but its influence on the yield stress is not significant [79,80].…”
Section: Morphologymentioning
confidence: 99%
“…Magnetic nanoparticles greatly reduce gravitational settling by increasing the viscosity and density of the medium and by the so called "halo" structure formation, as a consequence of gathering magnetic nanoparticles around the large micrometer range particles due to magnetic and van der Waals attraction. A new type of magnetorheological fluid was developed [65] based on a carbon nanotube and magnetite (CNT/Fe3O4) nanocomposite. The MR fluid contains CNTs covered with a layer of soft magnetic magnetite nanoparticles.…”
Section: Magnetorheological Fluidsmentioning
confidence: 99%